The Role of Youth Parliaments in Increasing Youth Participation (International and Uzbekistan Examples) - Khudaynazarov Orinbaevich (Penerbit Jurnal Indonesia, 2024)
The article examines the role of youth parliaments in increasing the participation of young people in political processes. Also, the article describes the practical experiences of the youth parliaments in the world and the practical measures taken, as well as the practical work carried out by the youth parliament in Uzbekistan. Some problems in the activity of youth parliaments in increasing the participation of young people in political processes, conclusions, suggestions and recommendations for further improvement of its activity are given and socio-political analysis is made.